2016
DOI: 10.3892/ol.2016.4928
|View full text |Cite
|
Sign up to set email alerts
|

Deguelin inhibits proliferation and migration of human pancreatic cancer cells in vitro targeting hedgehog pathway

Abstract: Abstract. Pancreatic cancer (PC) is a highly lethal malignancy with few effective therapies. Deguelin, a natural compound of the flavonoid family of products, has been reported to have an inhibitory effect on various cancers. In the present study, we investigated whether deguelin had antitumor efficacy in PC. Deguelin treatment was observed to inhibit growth and induce apoptosis in two PC cell lines (Bxpc-3 and Panc-1). In addition, it inhibited migration and invasion in these two cell lines. The activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Consistently, a recent study showed that deguelin could inhibit cancer cells growth with apoptosis being involved [17,25,26]. Furthermore, we found that deguelin promotes accumulation of autophagosomes.…”
Section: Discussionsupporting
confidence: 90%
“…Consistently, a recent study showed that deguelin could inhibit cancer cells growth with apoptosis being involved [17,25,26]. Furthermore, we found that deguelin promotes accumulation of autophagosomes.…”
Section: Discussionsupporting
confidence: 90%
“…Non‐small cell lung cancer accounts for the major percentage of lung cancer cases and has a poor prognosis. In recent years, drug resistance in tumor treatment has been a concern for patients; however, more in‐depth studies on anti‐tumor mechanisms and components, such as deguelin, are being studied in different cancers . In this study, we demonstrated that deguelin inhibited NSCLC cell metastasis and EMT by downregulating NEK2 expression.…”
Section: Discussionmentioning
confidence: 67%
“…Deguelin, a rotenoid extracted from Mundulea sericea , has been documented to possess anti‐tumor activities for several cancers, including pancreatic, lung, breast and colon cancers . Accumulating evidences have shown that deguelin is involved in different biological processes, such as apoptosis, proliferation, and migration/invasion . A recent study showed that low‐dose deguelin inhibited oral cancer migration and invasion by regulating tumor necrosis factor‐α‐induced nuclear factor‐κB activity and matrix metallpproteinase‐2 (MMP‐2), and in human osteosarcoma cells by inhibiting MMP‐2/MMP‐9 expression .…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, deguelin impedes carcinogenesis by 1) inducing cell apoptosis, 2) inhibiting tumor cell propagation, and 3) preventing malignant transformation of tumors. 16,17 Crucial oncogenic pathways likely targeted by deguelin are the phosphoinositide 3-kinase (PI3K)/Akt pathway, [18][19][20][21][22][23][24][25][26] the Wnt signaling pathway, 27,28 the epidermal growth factor receptor (EGFR) and c-Met signaling pathway, 29 the epithelial-to-mesenchymal transition (EMT) pathway, 30 the hedgehog signaling pathway, 31,32 and angiogenesis-related pathways. 33 In addition, deguelin has been identified as an Aurora B kinase inhibitor that exhibits a potent antitumor effect in human esophageal squamous cell carcinoma.…”
Section: Key Proliferative and Angiogenic Pathways Targeted By Deguelinmentioning
confidence: 99%